Legal Horizons in Global Commerce: Sovereign Dynamics, State-Owned Enterprises, and Dispute Resolution Approaches in International Law - Widiarty, Wiwik Sri; Kamal, Abu Hena Mostofa (UNISSULA, 2022)
This research explores the legal standing of a country as a distinct entity in international trade law, endowed with sovereign authority to regulate the inflow and outflow of goods and services across its borders. Emphasizing the multifaceted role of a country as a regulatory entity within the realm of international trade, this study specifically delves into its position as a buyer. The investigation centers on elucidating the dispute resolution mechanisms available to a country acting in the capacity of a buyer. As an autonomous legal subject in the sphere of international trade, a country possesses the inherent right to oversee and control the movement of goods and services, a prerogative that extends to its role as a buyer in commercial transactions. Notably, the research unveils that a country can function as a buyer through state-owned enterprises (SOEs), which bear the responsibility of reporting their trade activities to the Council for Trade in Goods. This process is instrumental in upholding the principles of non-discrimination and ensuring transparency in trade practices. Consequently, the trade relations between SOEs and individual traders can be characterized as contractual agreements, affording the application of principles such as freedom of contract. This includes the autonomy to select applicable laws and opt for specific forums for dispute resolution, underscoring the nuanced legal dynamics inherent in the interactions between countries and individual traders in the international trade landscape.